The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.4025/actascitechnol.v34i3.8790
|View full text |Cite
|
Sign up to set email alerts
|

Storage of strawberries (Fragaria ananassa L.) cv. ‘Oso Grande’, subjected to 1-MCP

Abstract: ABSTRACT. This study aimed to investigate the influence of 1 -methylcyclopropene (1-MCP) on the substances involved in the softening of strawberry, cultivar Oso Grande, stored at room temperature, from the municipality of Itutinga, State of Minas Gerais. The parameters evaluated were: firmness, total pectin, percentage of solubilization, activities of the enzymes pectinmethylesterase (PME) (EC 3.1.1.11) and polygalacturonase (PG) (EC 3.2.1.15). It was concluded that 1-MCP delayed the softening of the fruits, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
1
4
0
1
Order By: Relevance
“…ClO 2 and 1-MCP group (P [ 0.05). This result was in agreement with the previous reports, wherein both 1-MCP and ClO 2 had the ability to maintain the firmness of fruits such strawberry (Sliva et al 2012), nectarine (Ziliotto et al 2008), and plum (Chen and Zhu 2011), and a better effect on firmness retention was observed with their combination as compared with their single treatment.…”
Section: Firmnesssupporting
confidence: 93%
See 1 more Smart Citation
“…ClO 2 and 1-MCP group (P [ 0.05). This result was in agreement with the previous reports, wherein both 1-MCP and ClO 2 had the ability to maintain the firmness of fruits such strawberry (Sliva et al 2012), nectarine (Ziliotto et al 2008), and plum (Chen and Zhu 2011), and a better effect on firmness retention was observed with their combination as compared with their single treatment.…”
Section: Firmnesssupporting
confidence: 93%
“…Several studies have reported that 1-methylcyclopropene (1-MCP) may maintain the quality attributes of strawberries (Sliva et al 2012) with no effect on the overall fruit acceptability; however, 1-MCP may slightly increase rot development (Bower et al 2003). Therefore, sterilization treatment was necessary for strawberry storage.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the decay rate was lower compared to the control group. In another study, Silva et al (2012) attempted to identify the reason for the delayed firmness of the 1-MCP-treated strawberries. They observed that the activities of enzymes pectin methylesterase and PG, which are responsible for the degradation of cell wall pectins in the fruits, were lower in strawberries treated with 100 nL/L concentration of 1-MCP for 2 h. Langer et al (2022) treated fresh strawberries with 1 μL/L concentration of 1-MCP for 10 h at 22 • C and then stored them at 4 • C for 10 days.…”
Section: Chemical Treatmentsmentioning
confidence: 99%
“…3. Sadržaj ukupnih organskih kiselina u jagodama tretiranim različitim koncentracijama 1-MCP pri različitim uslovima tretiranja Titratable acidity in strawberries treated with various 1-MCP concentrations at different treatment conditions U studiji tretiranja Oso grande jagoda sa 0.1 ppm 1-MCP 2 sata na sobnoj temperaturi je zaključeno da se usporava gubitak čvrstoće tretiranih jagoda u odnosu na kontrolne, jer je tretman uzrokovao smanjenje aktivnost enzima poligalakturonaze i pektinmetilesteraze (Silva et al, 2012). Primjena 1 ppm 1-MCP u toku 24 h na 5 o C nije uticao na čvrstoću ploda praćenu tokom 12 dana na 5 o C nakon tretmana (Aguayoa et al, 2006).…”
Section: Total Anthocyanin Content In Strawberries Treated With Variounclassified